(untitled) (Research, Society and Development, 2020)
This study brings a didactic proposal that contributes to the formation of a citizen participant and aware of his role in society and of a teaching that must be developed in a relevant social context in order to provide meaningful learning. The proposal is for an exploratory research descriptive of the proposal for a UEPS based on the CTS approach. Aiming to propose, within the school context, the theme of energy sources using the CTS approach through a Potentially Significant Teaching Unit (UEPS), a teaching methodology proposed by Moreira (2011) for contextualized learning on this theme establishing relationships between Science, Technology, Society in an analysis within the proposals suggested by the skills to be worked on at BNCC. After analyzing the steps and objectives of each segment in order to think about the possibility of application in the classroom, it is understood that the proposal has great pedagogical possibilities to contribute to the teaching-learning process, meeting the objective proposed by this research. It is believed in the success of this proposal, since the planned UEPS met the guidelines based on the author and contemplates the theme foreseen for the curricular component. The use of this sequence of activities for science education arouses the student’s curiosity and promotes the reflective emancipation of their experience, invests in the meaning of the concepts and moves towards the formation of a critical and active citizen in society, meeting those provided by the BNCC, from work with a CTS focus.